Analysis of the Distribution of the Family Hope Program (PKH) on the Welfare Level of the Lompoe Parepare Community - umaima umaima; nuraefih nuraefih (IAIN Palopo, 2023)
The Family Hope Program is one of the social protection programs in Indonesia in the form of social assistance. This program is one of the government's efforts to accelerate poverty alleviation and specifically aims to break the intergenerational poverty chain.This study aims to analyze the distribution in Lompoe Parepare Village. This research uses theological and phenomenological approaches. In collecting research data using descriptive qualitative research methods. The data collection techniques used are observation, interviews, and documentation. The results of this studyin the welfare of society is carried out in detail and in accordance with applicable regulations or according to procedures set by the central government. Second, distribution in the Lompoe Village, it can be said that the distribution is not comprehensive but it is right on target. Third, based on an Islamic economic perspective it is not in accordance with the distribution in Islam because it does not fulfill two principles, namely the principles of equity and solidarity.